Nepotisme, ketimpangan sosial, dan penegakan hukum selektif dalam kasus korupsi elite politik: Kajian literatur - Awalul Hanafi; M Rifki Siregar (Albayan Journal of Islam and Muslim Societies, 2026)
Nepotism, social inequality, and selective law enforcement in cases of political elite corruption remain significant challenges to the realization of justice and good governance in Indonesia. This study aims to examine the relationship between nepotism, social inequality, and selective law enforcement in the context of political elite corruption through a literature review approach. The study employs qualitative library research by analyzing relevant academic publications published within the last five years, complemented by several foundational theoretical sources. The findings reveal that nepotism contributes to the concentration of power and resources among certain political groups, thereby weakening meritocratic principles and creating unequal access to public opportunities. Such conditions foster social inequality and facilitate corrupt practices among political elites. Furthermore, selective law enforcement exacerbates these problems by providing unequal legal treatment between political elites and ordinary citizens, which undermines public trust in legal institutions and weakens the rule of law. The study argues that nepotism, social inequality, and selective law enforcement are interconnected phenomena that reinforce one another and contribute to the persistence of political corruption. Therefore, strengthening transparency, accountability, merit-based governance, and impartial law enforcement is essential to promoting social justice and improving the effectiveness of anti-corruption efforts in Indonesia. This study contributes to a broader understanding of the structural relationship between political power, corruption, and social inequality within the Indonesian context.